Pengamalan Pancasila pada Siswa Sekolah Dasar - Suhartini Suhartini; Husnul Khotimah; Prita Indriawati (Abdimas Universal, 2023)
Pancasila is one of the foundations of social life to build humane citizens. The inculcation of Pancasila values ​​needs to be done from an early age so that when he becomes an adult, the national character is attached to him. Socializing the practice of Pancasila to elementary school students is a way that can be taken to instill Pancasila values ​​as the basis of the state. Students as agents of change, guardians of values, successors of the nation, moral strength, and social control need to contribute to the inculcation of Pancasila in students. The purpose of this activity is that students provide an understanding of Pancasila as well as education on the practice of Pancasila in everyday life to students. This activity was carried out by 7 students of the Mathematics Education study program with their respective division of tasks. The target of this activity is the fourth grade elementary school students. Data is collected through observation when students carry out activities in class. The result of this activity is that students listen well to the presentation of the material because they are interested in information on the form of Pancasila practice. In addition, students are enthusiastic about participating in activities because external parties or students deliver the material.